LOCAL GOVERNMENT UNITS SUPPORT PROGRAMS TO SPORTS COMPETITION IN SAMAR DIVISION - Eduardo C. Montejo Jr; Rosybelle T. Sablad (Western European Studies, 2023)
Sports training and providing sports materials among elementary student-athletes are imperative in winning any sports competition. Explicitly, this study delved into investigating the Local Government Units support programs for sports competition in Samar Division and Catbalogan City Division, Province of Samar. Imperative data were taken from the eighty-four (84) respondents of the two (2) divisions through a mixed method of research. An in-depth interview was employed utilizing the Husserlian descriptive phenomenology to obtain the results for the qualitative research. A survey was conducted to triangulate the responses. Results revealed that year 2021 garnered the highest amount of financial support amounting to ₱ 2,825,807.15
Keywords: local government units; sports programs; competition